Penguatan Tata Kelola Arsip Keluarga sebagai Strategi Mitigasi Bencana di Desa Teluk Provinsi Banten - Eha Saleha; Rahmat Hidayat; Vivi Indra Amelia Nasution; Meita Istianda; Darmanto; Arwanto Harimas Ginting (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2025)
Teluk Village in Labuan District, Pandeglang Regency, Banten Province, is a flood-prone area with water levels reaching 1.5–3 meters, potentially damaging important family records such as birth certificates, diplomas, and land certificates. This situation is exacerbated by low community literacy regarding archive management and minimal safe storage practices. This community service activity aims to train village communities in managing family archives in Teluk Village and describe mentoring strategies through a one-day workshop on manual and digital archive management. The activity was carried out using a participatory approach through observation, short interviews, tool demonstrations, and archive digitization practices. Analysis was conducted descriptively through processing field findings and participant feedback. The results showed that most residents store archives in unsafe places (under mattresses, damp wooden cabinets), do not have archive classifications, and have never digitized documents. The workshop increased participants' understanding of important archive types, digitization steps, and the use of mobile-based digital storage. Indicators of success were seen in increased participant knowledge (85%), basic digitization practice skills (78%), and the use of waterproof plastic folders as initial storage facilities. This study emphasizes the importance of disaster mitigation-based family archive management and the need for further training to ensure the sustainability of archive digitization practices in disaster-prone communities.